ASSESSMENT OF THE IMPACT OF TRADE WITH POLAND ON UKRAINE'S ECONOMIC GROWTH - Iryna Babets (Izdevnieciba "Baltija Publishing", 2023)
The purpose of the study is to assess the impact of Ukrainian-Polish trade in goods on the economic growth of Ukraine. The tasks of the study include an analysis of the dynamics and structural changes in Ukraine's trade in goods with Poland, an assessment of the impact of the main indicators of the volume of trade with Poland on Ukraine's economic growth, and a study of the relationship between the indicators of Ukraine's economic growth and changes in the volume of exports and imports of the main groups of goods in trade with Poland. In the course of the research, the method of regression analysis was used to determine the influence of the total volume of exports and imports and the product structure of bilateral trade on the economic growth of Ukraine. As a result of the regression analysis, the dependence of Ukraine's economic growth on imports of goods from Poland was revealed, and the impact of changes in the volume of Ukraine's exports of goods on Ukraine's economic growth was statistically insignificant. The study confirmed the dependence of Ukraine's economic growth on changes in the volume of iron ore exports to Poland and imports of cosmetic industry products from Poland. A statistically insignificant influence of exports and imports of other main groups of goods in trade with Poland on Ukraine's economic growth was found. In the period of post-war reconstruction, the deepening of Ukrainian-Polish cooperation in the implementation of joint infrastructure and industrial projects, which provide for the establishment of production of necessary products using materials and components imported from Poland, can become an important component of the economic growth of Ukraine.